Federalismo fiscal e petróleo no Brasil e no mundo - Sérgio Wulff Gobetti (Instituto de Pesquisa Econômica Aplicada (IPEA), 2011)
– This paper tries to contribute to the current discussion on sharing rules of royalties in Brazil from theoretical and empirical reflections about fiscal federalism and from a comparative analysis of the experiences of oil producing countries that, as our example, organize themselves like federations. The analysis is based on studies joined in a international project named Oil and Gas in Federal Systems and shows that the petroleum ownership and revenue arrangement vary across countries because it depends of history and political culture rather than philosophical and technical arguments of each one. Indeed, the Brazilian model of sharing oil revenues from offshore, that was conceived in 1985 and consolidated in 1997, must be interpreted in the context of the process of fiscal decentralization and political bargains that marked the transition from military dictatorship to democracy, when the oil production was inexpressive. This pattern seems unsustainable if we consider the perspectives and challenges of pre-salt discoveries, that claim for a larger degree of centralization of oil revenues, as the example of other countries where the petroleum has economic relevance.
Keywords: H73; H77; N50; 330; Finanzbeziehungen; Erdölgewinnung; Öffentliche Einnahmen; Brasilien